Penerapan Alat Peraga Trigonometri Sudut Istimewa Bagi Siswa pada SMK Yabri Terpadu Pekanbaru - Nur Hadziqoh; Icha Fatwasauri; Puspita Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The problem that is faced by students is the difficulty of students to understand in learning mathematics. It affected the interest of students in learning mathematics. One of the factors is the one-way method in teaching. The direction of information is from the teacher to the students that makes students passive in class. Most students have a low imagination to understand abstract and invisible mathematical concepts. The use of concrete objects as intermediaries in the learning process is an alternative to delivering interesting and interactive learning in the classroom. One of them is by using a display tool. The aim of this activity is to provide learning alternatives that make it easier for students to understand the Trigonometry Special Angles and to develop critical thinking of students during the learning process. The implementation of this activity is to apply a display tool as a Learning Tool In Trigonometry Special Angles. This activity was carried out on class XI students of SMK Yabri Terpadu Pekanbaru. This activity is carried out in three stages that are preparation, implementation, and evaluation. From the results of this activity, an evaluation shown that the use of Trigonometry Special Angles Display Tool in the learning process, make students easier to understand the learning trigonometry special angle and make the learning process more interesting and interactive.